INSERÇÃO URBANA NO PMCMV SOB A PERSPECTIVA DO USUÁRIO - Berleze, Angélica; Silvoso, Marcos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article evaluated the satisfaction of residents of housing complex in Chapecó/SC, in relation to the urban insertion and proximity to urban equipment. The approach was based on multiple post-occupancy evaluation methods, walkthrough, questionnaire and focus group. The results indicate a low level of satisfaction with the location of the neighborhood and with the services and equipment offered in the surroundings, which may impact on the well-being of the population and contribute to the reduction of their quality of life.